The Principle of Da'wah at-Tafhim la Talqin in the Da'wah of Arrazy Hasyim from the Perspective of Jum'ah Amin 'Abdul Aziz - Marya Ulfa; Lilis Muchlisoh; Achmad Zaki Ghufron; Maftukhatul Azizah; Moh. Ali Aziz; Alfiansyah Husin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study analyzes the principle of da'wah at-Tafhim la Talqin in Arrazy Hasyim's da'wah on Youtube entitled